[3-Hydroxy-N′-(2-oxidobenzylidene)-2-naphthohydrazidato-κ3O,N,O′]tris(pyridine-κN)nickel(II) pyridine trisolvate - Jian-Min Dou; Da-Qi Wang; Da-Cheng Li; Wen-Jun Kang; Shi-Zhu Sun (Acta Crystallographica Section E, 2008)
The asymmetric unit of the crystal structure of the title complex, [Ni(C18H12N2O3)(C5H5N)3]·3C5H5N, contains two independent NiII complex molecules and six uncoordinated pyridine molecules. Each NiII atom is coordinated by two O and four N atoms, from three pyridine and a chelating 3-hydroxy-N′-(2-oxidobenzylidene)-2-naphthohydrazide dianionic ligand, with a distorted octahedral geometry. Intramolecular O—H...N hydrogen bonding exists in both complex molecules but no intermolecular hydrogen bonding is observed in the crystal structure.